2017
DOI: 10.1163/15718182-02503009
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Children’s Views in Finnish Court Decisions Regarding Care Orders

Abstract: The article examines the representation of children’s views in Finnish court decisions regarding care orders. It explores how written court decisions recognise, address and use children’s views in care order decisions and compares the results with a similar study conducted in Norway. In the literature, both countries are portrayed as having a child-orientated child welfare system. Based on the analysis of 36 court decisions in Finland, it is argued that children’s views are narrowly represented and used in wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…This could be one way to improve participation for younger children. On the other hand, previous research shows that an age limit could be important, as participation can increases for children over the specific age limit [De Godzinsky, ; Pösö & Enroos, ; Socialstyrelsen, ]. In addition, if there were no specific age limit, the question of what competence the child needs and who should be responsible for assessing when a child is sufficiently mature still needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be one way to improve participation for younger children. On the other hand, previous research shows that an age limit could be important, as participation can increases for children over the specific age limit [De Godzinsky, ; Pösö & Enroos, ; Socialstyrelsen, ]. In addition, if there were no specific age limit, the question of what competence the child needs and who should be responsible for assessing when a child is sufficiently mature still needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…It was also more common that the views of older children (14–17 years old) appeared in the judgment [De Godzinsky, ]. Another study from Finland that explored how written court decisions recognize, address, and use children's views found that the older the child, the more attention was given to his/her views, either directly or indirectly [Pösö & Enroos, ].…”
Section: Theoretical Perspective and Previous Research On Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…One feature of childcentered CW organizations is that children's rights, interests and needs are considered as essential elements in service-provision. Children are given the opportunity to express their views and opinions and to be involved in matters concerning them (Pösö and Enroos 2017). This systematization has been criticized for being limited to high-income countries and for not being sufficiently nuanced, and for inadequately acknowledging cultural complexity and different CW contexts (Connolly et al 2014: Waldock 2016.…”
Section: The Various Contexts Of Child Welfare Servicesmentioning
confidence: 99%
“…3. See Peters (2018) for reflections on the voice, story and dignity of the child in relation to hearing children in child protection, Leviner (2018) on the need to rethink children's participation in the Swedish child protection system, and Pösö and Enroos (2017) on the narrow representation and use of children's views in Finnish care orders. 4.…”
Section: Notesmentioning
confidence: 99%